Keterlibatan Orang Tua Dalam Pembentukan Karakter Religius Peserta Didik di SD Islam Almadina, MI Al Khoiriyyah 2 dan SDN Purwoyoso 02 Semarang - Santoso, Alek Budi; Wahib, Abdul; Suja’i, Suja’i (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research aims to describe and explain parental involvement in the formation of children's religious character at SDI Al Madina, MI Al Khoiriyyah 2, and SDN Purwoyoso 02 Semarang. This research uses a descriptive qualitative approach to describe parental involvement in the formation of children's religious character at SDI Al Madina, MI Al Khoiriyyah 2, and SDN Purwoyoso 02 Semarang. Data was obtained through observation, in-depth interviews and documentation, and analyzed using reduction, display and conclusion techniques. The results show the effectiveness and differences in the approaches used by each school in forming children's religious character. This research succeeded in describing parental involvement in the formation of religious character at SDI Al Madina, MI Al Khoiriyyah, and SDN Purwoyoso 02, including parenting, volunteering, and other school activities. The religious characters that are instilled include diligent prayer, recitation of the Koran, devotion to parents, independence, responsibility, care for the environment, honesty, tabligh, tolerance and discipline. The methods for forming religious character used are habituation, example, as well as advice and motivation. Each school shows similarities and differences in the application of these religious values, but in general the character formed is in accordance with national character and core learning competencies. In conclusion, comprehensive parental involvement is very important in strengthening the habituation of religious values ​​in children.